Low-temperature fabrication of NASICON-type LATP with superior ionic conductivity. Issue 24 (15th December 2022) - Shen, Shao-Peng; Tang, Geng; Li, Hong-Ji; Zhang, Liang; Zheng, Jin-Chi; Luo, Yuan; Yue, Jun-Pei; Shi, Yongzheng; Chen, Zhe
Abstract: NASICON-type Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) has attracted much attention as a fast lithium-ion conductor for all-solid-state lithium-based batteries. However, the large grain-boundary resistance and high sintering temperature above 950 °C for pure LATP electrolytes hinder their practical application in lithium-based batteries. Here, a low-temperature preparation approach for the superionic conductor LATP electrolyte with sintering aids is proposed. By introducing sintering aids Li3 PO4, LiBO2 ·0.3H2 O, and binary 0.32Li3 PO4 -0.68LiBO2 ·0.3H2 O, LATP-based pellets can be fabricated at optimized sintering temperatures below 900 °C. The resultant LATP-based pellets maintain a high relative density and homogeneous microstructure, which arises from the sintering aid to facilitate the grain rearrangement and fill the interstices between grains. The LATP pellets using sintering aid Li3 PO4 achieve a high ionic conductivity of 5.2 × 10 −4  S cm −1 at a low temperature of 800 °C, 7.3 times that (7.1 × 10 −5  S cm −1 ) of pure LATP pellets sintered at 950 °C, which demonstrates the effectiveness of low-temperature preparation approach to reducing the preparation cost and optimizing the ionic conductivity of LATP-based electrolytes.